A Computational Microspectrometer Based on Binary-Image-Generated Freeform Metasurfaces for Spectral Sensing - Chao Hu; Xingyan Zhao; Yang Qiu; Shaonan Zheng; Qize Zhong; Yuan Dong; Ting Hu (IEEE Photonics Journal, 2024)
In the trend of spectrometer miniaturization, the design of combining computational imaging with the metasurfaces has been proved to be an efficient and feasible solution. Nevertheless, determining the optimal filter array design remains a compelling subject for ongoing research. A computational microspectrometer consisting of a planar array of broadband optical filters is proposed, which are formed by low-loss freeform dielectric metasurfaces. Diverse metasurface designs are obtained by using binary graph generation technology, and rich spectral responses are obtained. The final performance of microspectrometer depends on the trade-offs between reconstruction time, relative error, footprint, and resolution. To optimize these trade-offs, we have improved the existing freeform metasurface design scheme and optimized the filter array design. Simulation results show the proposed microspectrometer can successfully reconstruct the spectra over the 380 to 680 nm spectral range with a resolution of 1 nm. In summary, we propose an integrated design including meta-pixel design, filter combinations and simulation test flow, which leads to an impressive performance microspectrometer.